EXTH-74. ATR INHIBITION IN EXPERIMENTAL GLIOMA. (14th November 2022) - Walter, Bianca; Schnabel, Leonard; Hirsch, Sophie; Stahl, Aaron; Haeusser, Lara; Tsiami, Foteini; Kuhlburger, Laurence; Nahnsen, Sven; Templin, Markus; Schenke-Layland, Katja; Merk, Daniel; Tabatabai, Ghazaleh
Abstract: Glioblastoma are incurable primary tumors of the central nervous system. Novel treatment options are urgently needed. Recently, we investigated molecular effects of disrupting the (b)HLH network, a frequently altered and tumor-promoting transcriptional network in glioma, by introducing a dominant-negative variant of the E47 protein. The identified downstream anti-tumor effects included the DNA damage response pathway. In the present study, we aimed at investigating the anti-glioma effects of ATR inhibition in vitro and in vivo with a particular focus on treatment-induced vulnerabilities and potential combination therapies. We performed acute cytotoxicity, clonogenic survival assays, flow cytometry-based determination of cell cycle status and apoptosis induction in human and murine glioma cell lines in vitro, and investigated tumor growth in the SMA560/VMDk syngeneic mouse model in vivo . Furthermore, we applied RNA sequencing, DigiWest protein profiling analyses and genome-wide CRISPR/Cas9 loss-of function and activation screens to determine potential combination therapies. Combination treatments were further analyzed for synergism by the Bliss and ZIP synergy models. ATR inhibition in glioma cells resulted in reduced viability and clonogenic survival. However, differential patterns of gene expression deregulation (e.g. p53 signaling) and differing modes of cell cycle arrest in distinct glioma model systems argue for a substantial heterogeneity with regard to response to ATR inhibition. Based on our data we designed combinatorial treatments. We will present novel insights into promising combinatorial treatments using ATR inhibition and their underlying molecular mechanisms.